The Noradrenergic Locus Coeruleus as a Chronic Pain Generator - Taylor, Bradley K. (J Neurosci Res, 2016)
Central noradrenergic centers such as the locus coeruleus are traditionally viewed as pain inhibitory; however, complex interactions among brainstem pathways and their receptors modulate both inhibition and facilitation of pain. In addition to the well-described role of descending pontospinal pathways that inhibit spinal nociceptive transmission, an emerging body of research now indicates that noradrenergic neurons in the locus coeruleus (LC) and their terminals in the dorsal reticular nucleus (DRt), medial prefrontal cortex (mPFC), spinal dorsal horn and trigeminal spinal nucleus caudalis (spVc) participate in the development and maintenance of allodynia and hyperalgesia after nerve injury. With time after injury, we argue that the balance of LC function shifts from pain inhibition to pain facilitation. Thus, the pain inhibitory actions of antidepressant drugs achieved with elevated noradrenaline concentrations in the dorsal horn may be countered or even superseded by simultaneous activation of supraspinal facilitating systems dependent on α(1)-adrenoreceptor in the DRt and mPFC as well as α(2)-adrenoreceptors in the LC. Indeed, these opposing actions may account in part for the limited treatment efficacy of tricyclic antidepressants and noradrenaline reuptake inhibitors such as duloxetine for the treatment of chronic pain. We propose that the traditional view of the LC as a pain inhibitory structure be modified to account for its capacity as a pain facilitator. Future studies are needed to determine the neurobiology of ascending and descending pathways and the pharmacology of receptors underlying LC-mediated pain inhibition and facilitation.